Experimental study on pore structure characteristics and thermal conductivity of fibers reinforced foamed concrete. - Lin Li; Wei Wang; Yu Wang; Dongxu Li; Mei-Ling Zhuang (PLoS ONE, 2023)
The pore structure characteristics and thermal conductivity of foamed concrete (FC) reinforced with glass fibers (GF), polyvinyl alcohol fibers (PVAF) and polypropylene fibers (PPF) were investigated experimentally in this article. Firstly, GF, PVAF or PPF with different mass fractions (0%, 1%, 1.5% and 2%) were added to the Portland cement, fly ash and plant protein foaming agent to prepare the FC. Then, SEM tests, dry density tests, porosity tests, and thermal conductivity tests were carried out on FRFC. Later, the adhesion of GF, PVAF and FFF with different mass fractions to the cementitious base was investigated by SEM images of FRFC. The pore size distribution, shape factor and porosity of FRFC were analyzed using Photoshop software and Image Pro Plus (IPP) software. Finally, the effects of different mass fractions and lengths of three types of fibers on the thermal conductivity of FRFC were discussed. The results indicated that proper fiber mass fraction can play a role of refining small pores and separating large pores, improving the structural compactness, reducing the pore collapse phenomenon and optimizing the pore structure of FRFC. The three types of fibers can promote the optimization of cellular roundness and increase the proportion of pores with diameters below 400 μm. The FC with larger porosity had smaller dry density. As the fiber mass fraction increased, the thermal conductivity performed a phenomenon of first decrease and then increase. The three types of fibers with 1% mass fraction achieved relatively low thermal conductivity. Compared with the FC without fibers, the thermal conductivities of GF reinforced FC, PVAF reinforced FC and PPF reinforced FC with 1% mass fraction were decreased by 20.73%, 18.23% and 7.00%, respectively.